Athlete's heart: a meta-analysis of the echocardiographic experience - Fagard, R. H. (International Journal of Sports Medicine, 1996)
Meta-analytical techniques were applied to selected echocardiographic reports on athlete's heart. The combined analysis of studies in which competitive long-distance runners were compared to matched nonathletic control subjects, revealed a 10% (p < 0.001) higher left ventricular internal diameter in the runners, an 18% (p < 0.001) thicker wall and an 8% (p < 0.05) greater relative wall thickness. In strength athletes these differences averaged +2.5% (p < 0.01), +15% (p < 0.05) and +12% (p < 0.05), respectively, and in cyclists +9% (p < 0.05), +29% (p < 0.01) and +19% (p <0.05). When compared to their respective controls, left ventricular mass was larger by 64% (p < 0.01) in cyclists, 48% (p < 0.001) in runners and 25% (p < 0.05) in strength athletes. There were no differences in left ventricular systolic or diastolic function at rest. The meta-analysis of longitudinal studies, in which athletes were assessed in active and inactive periods, suggested that at least part of the differences from nonathletes can be ascribed to the training per se. In conclusion,the classification of left ventricular hypertrophy in athletes as eccentric or concentric has to be considered as a relative concept, most likely related to the fact that training regimens and/or sports activities are not exclusively of the dynamic or static type but comprise both components to a variable extent.